Influência do hipotireoidismo gestacional experimental sobre a função cardiovascular da prole de ratas - Santos, Sheyla Oliveira (2012)
Gestational hypothyroidism is a prevalent disorder in pregnant women. We aimed to investigate the impact of experimental gestational hypothyroidism (EGH) on cardiovascular and autonomic nervous systems (ANS) in the offspring of rats. EGH was induced with methimazole (MMI) 0.02% in drinking water from day 9 of gestation until birth. Sixty days old offspring from MMI-treated dams (OMTD, n=13) or water-treated dams (OWTD, n=13) had femoral arteries surgically assessed for the measurements of heart rate (HR), mean (MAP), systolic (SAP) and diastolic arterial pressure (DAP), and spontaneous baroreflex sensitivity (BRS). To investigate the balance of ANS, we established the high (HF) and low frequency (LF) bands of pulse interval (PI) and LF band of SAP spectrum. OMTD had increased MAP (130.2±2.0 vs 108.8±3.0 mmHg, p < 0.001), SAP (157.3±2.9 vs 135.7±4.5 mmHg, p < 0.001) and DAP (109.7±1.9 vs 88.4±2.6 mmHg, p < 0.001) when compared to OWTD, and had lower HR (355.1±8.9 vs 386.8±9.2 bpm, p < 0.05). After spectral analysis of PI and SAP, only LF band of SAP spectrum was higher (7.2±0.8 vs 4.0±0.6 mmHg2) in OMTD under spontaneous condition. Despite bradicardia, EGH promotes spontaneous hypertension in 60 days old offspring, probably due to increased sympathetic activity to vessels, which is suggested by the higher LF of SAP. These findings suggest a critical role of maternal THs in the development of fetal cardiovascular and autonomic nervous system.